Constitutive modelling and numerical simulation of dynamic behaviour of asphalt-concrete pavement - ZBICIAK, A. (Engineering Transactions, 2014)
The main objective of the paper is to present a simple constitutive model suited for dynamic simulation of asphalt-concrete mixtures. ABAQUS/Explicit FE software is used for this purpose. The model belongs to the class of overstress hypoelastic-viscoplastic materials, taking into account the effect of pressure-dependence on yielding. The implementation of constitutive relations formulated in the paper is done through user subroutine module VUMAT. The results of numerical simulation of dynamic behaviour of multilayer pavement structure, illustrating the applicability of the algorithm, is also discussed.